Dynamic form : how intermediality made modernism - Lewis, Cara L., 1983- (Cornell University Press, 2020)
"Dynamic Form offers a new conceptual and historical account of modernism through an emphasis on the intersecting domains of visual and narrative media. The project analyzes texts from the first five decades of the twentieth century alongside sculptures, paintings, photographs, and films in order to show how visuality and non-textual media inflect the shape and movement of modernist narratives. Presents a wide-ranging study of modernist inter-mediation that embraces references to fine-art objects and evocations of painterly genres, as well as visual motifs and modes of viewing and engaging with visual and plastic artworks. Chapters on works by Henry James, Mina Loy, Virginia Woolf, Gertrude Stein, and Evelyn Waugh demonstrate that literary modernism's imbrication with spheres of visuality not only permeates its experiments with form but also calls for a more capacious rethinking of the visual-verbal encounter"--